A Descriptive Analysis Review of the Literature on the Impact of Green Accounting on Sustainable Development Goals (SDGs) - Anthoni, Lukman; Winursito, Winursito; Kurniasih , Diah; Cahayasari, Rizki; Rosini, Iin (The Future of Education Journal, 2026)
Competition in the industry is increasing annually, leading industry players to compete in creating high-value-added products, but only a few industries are concerned about the environment. Green accounting has emerged in response to growing environmental concerns, as traditional accounting methods have been deemed inadequate in capturing environmental impacts. This study aims to provide evidence on the impact of implementing green accounting on sustainable development goals (SDGs). The approach used is descriptive qualitative, and data is collected through a literature search system or literature review. The results indicate that green accounting has a significantly positive effect on Sustainable Development Goals (SDGs).